Reading 1-2 Peter and Jude: a resource for students - Mason, Eric Farrel; Martin, Troy W. (Resources for biblical study, 2014)
Gathering Apostolic voices: who wrote 1 and 2 Peter and Jude? / Lewis R. Donelson -- The literary relationships among 1 Peter, 2 Peter, and Jude / Jeremy F. Hultin -- The epistolary rhetoric of 1 Peter, 2 Peter, and Jude / Duane F. Watson -- "Awaiting new heavens and a new earth": the apocalyptic imagination of 1/2 Peter and Jude / Kelley Coblentz Bautch -- Reborn to a living hope: a Christology of 1 Peter / Steven J. Kraft Chick -- Christians as babies: metaphorical reality in 1 Peter / Troy W. Martin -- Be holy, for I am holy: paraenesis in 1 Peter / Nancy Pardee -- Ethnicity, empire, and early Christian identity: social-scientific perspectives on 1 Peter / David G. Horrell -- Peter and postmodern criticism / Félix H. Cortez -- Peter in patristic literature / Andreas Merkt -- Biblical and nonbiblical traditions in Jude and 2 Peter: sources, usage, and the question of canon / Eric F. Mason -- Are the others too other? : the issue of "others" in Jude and Peter / Peter H. Davids -- Searching for evidence: the history of reception of the Epistle of Jude and 2 Peter / Wolfgang Grünstånudl and Tobias Nicklas